Unilateral eosinophilic cellulitis leading to implant extrusion after bilateral enucleation in a dog. Issue 2 (2nd February 2022) - Aronson, Riley J.; Pumphrey, Stephanie A.; Robinson, Nicholas
Abstract: A mixed breed dog underwent bilateral enucleation with orbital implant placement for secondary glaucoma. Subsequent unilateral implant extrusion occurred. An orbital mass histologically consistent with eosinophilic cellulitis was discovered. It may have developed secondary to communication between orbit and skin. Inflammatory processes mimicking neoplasia can cause implant loss post‐enucleation. Abstract : A mixed breed dog underwent bilateral enucleation with orbital implant placement for secondary glaucoma. Subsequent unilateral implant extrusion occurred. An orbital mass histologically consistent with eosinophilic cellulitis was discovered. It may have developed secondary to communication between orbit and skin. Inflammatory processes mimicking neoplasia can cause implant loss post‐enucleation.